Screening for anticoagulant substances in some marine macroalgae - De Lara-Isassi, Graciela; Alvarez-Hernández, Sergio; Quintana-Pimentel, Angélica (HIDROBIOLÓGICA, 2017)
The coagulation disorders have increased in the last decades and no new substances had been discovered that could regulate this illness. This fact makes the discovery of new anticoagulant substances a priority issue in research. Forty nine seaweed species collected off shore of several localities of Gulf of Mexico and Mexican Caribbean sea were screened in order to detect anticoagulant activity in both intrinsic and extrinsic pathways of clot formation. Standardized plasma coagulation tests (thrombin and prothrombin time) were used. Heparin, a sulphated glycosaminoglycan wide used in oral anticoagulant therapy, was used as reference in both proofs. The results showed that four species presented potent anticoagulant activity same as heparin in the two pathways: Anadyomene stellata, Caulerpa cupressoides (Chlorophyta), Lobophora variegata (Phaeophyta) and Liagora farinosa (Rhodophyta). Caulerpa paspaloides (Chlorophyta) was active only in the thrombin time test. Other seven species presented a slightly anticoagulant activity. We considered that algal extracts have substances capable of inhibit clot formation in the last steps of the coagulation cascade. The extracts could act preventing the conversion of prothrombin to thrombin, also they could act stopping the transformation of fibrinogen to convert it to fibrin o even in the polymerization of this last molecule. This is the first report of anticoagulant activity in Anadyomene stellata, Lobophora variegata and Liagora farinosa. We can concluded that these species can be considered as potentially alternative source of anticoagulant molecules.